On the question of the object crimes. (Journal of actual problems of jurisprudence, 2016)
In this article the author summarizes the conceptual approach of the object of crime. And what should be important to consider the Concept of the criminal code of the RK object of crime as the interests of the social subjects.
Keywords: object of the crime; the theory of the object crime